Tal vez hay una forma más rápida, pero aquí va uno. Deje que la suma de dinero se $S$. Tenemos
$$\frac{f(n)}{n(n+1)} = \frac{f(n)}{n}-\frac{f(n)}{n+1}$$
$$\implies \frac{f(2n)}{(2n)(2n+1)}+\frac{f(2n+1)}{(2n+1)(2n+2)} = \frac{f(2n)}{2n}-\frac{f(2n)-f(2n+1)}{2n+1}-\frac{f(2n+1)}{2n+2}$$
Ahora $f(2n+1) = f(2n)+1, \; f(2n) = f(n)$, por lo que podemos escribir:
$$\frac{f(2n)}{(2n)(2n+1)}+\frac{f(2n+1)}{(2n+1)(2n+2)} = \frac{f(2n)}{2n}+\frac1{2n+1}-\frac{f(2n)+1}{2n+2} \\ = \frac12\left(\frac{f(n)}n -\frac{f(n)}{n+1}\right)+\left(\frac1{2n+1}-\frac1{2n+2}\right)$$
$$\implies S = \frac12+ \frac12\sum_{n=1}^\infty \frac{f(n)}{n(n+1)}+\sum_{n=1}^\infty \left(\frac1{2n+1}-\frac1{2n+2}\right) $$
$$\implies 2S = 1 + S + 2\log 2 -1 \implies S = 2\log 2 \approx 1.386$$